Between Fraud and Hope: Stem Cell Research in Korea after the Hwang Affair. Issue 2 (1st June 2018) - Kim, Myungsim; Kim, Jongyoung; Bak, Hee-Je
Abstract: This study analyzed the influence of the Hwang scandal on the stem cell research community and research governance systems in South Korea. In contrast to the claims of some critics that the fraud scandal might raise doubts about Korean stem cell science, the impact of the Hwang scandal on publications by Korean stem cell researchers in international scientific journals proved limited, with only a temporary halt in research and publications. On the one hand, Korea's scientific community has moved toward the ethical turn through which the Korean government tightened its research-ethics standards and regulations. On the other hand, the government and scientific community remain hopeful about stem cell research. Consequently, the politics of hope have led to the quick recovery of Korean stem cell science from the potential damage caused by the Hwang scandal. The scandal accelerated the South Korean government's efforts toward research ethics reform: it mandated universities and research institutes to create and strengthen institutional review boards and other research-integrity committees. In addition, the Korean government, maintaining its optimism about the economic value of stem cell science, continued to fund stem cell research. Despite the seemingly prompt recovery from the scandal, however, stem cell research governance systems in Korea face a serious new challenge: the ethical and safety concerns associated with the rapid commercialization of stem cell science. Therefore, this article views the changes in the scientific community as a process of conflict and negotiation between the accountability crisis in the Korean scientific community and the politics of hope in science.